Addition of Sulfonic Acids to Terminal Alkynes Catalyzed by a Rhodium Complex: Ligand Concentration‐Controlled Reaction Selectivity. Issue 10 (8th August 2013) - Yang, Yong; Moschetta, Eric G.; Rioux, Robert M.
Abstract A Rh‐catalyzed process for the regioselective formation of vinyl sulfonate esters in moderate to high yields through the hydrosulfonation of alkynes with sulfonic acids has been developed. Our synthetic approach is capable of adding a variety of alkynes to a set of sulfonic acids and is amenable to different phosphorus ligands, solvents, and Rh precursors. We control the chemo‐ and regioselectivity of the reaction to the Markovnikov vinyl sulfonate ester by tuning the concentration of the exogenous ligand, PPh3, which forms the active RhP species in situ. At lower PPh3 concentrations, the reaction favors the formation of vinyl sulfonate esters, whereas at higher PPh3 concentrations, the reaction favors the formation of vinylphosphonium salts. We perform Hammett analyses and kinetic isotope effect experiments to determine the steps of the catalytic mechanism. Reaction data for substituted acetylenes indicates syn and anti addition occur across the triple bond. Experiments performed with the vinylphosphonium salt as the exogenous ligand determined that the formation of the salt was not a necessary step in the catalytic mechanism for the direct formation of the vinyl sulfonate esters.